Openness and Financial Development in China: The Political Economy of Financial Resources Distribution. Issue 9 (1st September 2016) - Luo, Yu; Zhang, Chengsi; Zhu, Yueteng
ABSTRACT: This paper examines the impact of openness on financial development in China. We use two sets of indicators of financial development to distinguish size and efficiency for both bank and capital market sectors as aspects of financial development in 30 provinces of China over the period from 2000 to 2009. The empirical results suggest that trade and financial openness exert positive impact on financial efficiency but negative impact on the size of financial development for both the indirect and direct financial sectors. The results confirm a mismatch problem between the distribution in the types of trading companies and the allocation of financial resources in China.